Efficacy of genotype-matched Newcastle disease virus vaccine formulated in carboxymethyl sago starch acid hydrogel in chickens vaccinated via different routes - Mahamud, Siti Nor Azizah; Bello, Muhammad Bashir; Ideris, Aini; Omar, Abdul Rahman (The Korean Society of Veterinary Science, 2022)
Background: The commercially available Newcastle disease (ND) vaccines were developed based on Newcastle disease virus (NDV) isolates genetically divergent from field strains that can only prevent clinical disease, not shedding of virulent heterologous virus, highlighting the need to develop genotype-matched vaccines. Objectives: This study examined the efficacy of the NDV genotype-matched vaccine, mIBS025 strain formulated in standard vaccine stabilizer, and in carboxymethyl sago starch-acid hydrogel (CMSS-AH) following vaccination via an eye drop (ED) and drinking water (DW). Methods: A challenge virus was prepared from a recent NDV isolated from ND vaccinated flock. Groups of specific-pathogen-free chickens were vaccinated with mIBS025 vaccine strain prepared in a standard vaccine stabilizer and CMSS-AH via ED and DW and then challenged with the UPM/NDV/IBS362/2016 strain. Results: Chickens vaccinated with CMSS-AH mIBS025 ED (group 2) developed the earliest and highest Hemagglutination Inhibition (HI) NDV antibody titer (8log2) followed by standard mIBS025 ED (group 3) (7log2) both conferred complete protection and drastically reduced virus shedding. By contrast, chickens vaccinated with standard mIBS025 DW (group 5) and CMSS-AH mIBS025 DW (group 4) developed low HI NDV antibody titers of 4log2 and 3log2, respectively, which correspondingly conferred only 50% and 60% protection and continuously shed the virulent virus via the oropharyngeal and cloacal routes until the end of the study at 14 dpc. Conclusions: The efficacy of mIBS025 vaccines prepared in a standard vaccine stabilizer or CMSS-AH was affected by the vaccination routes. The groups vaccinated via ED had better protective immunity than those vaccinated via DW.